Examining MSME Business Performance in Central Java: The Role of Entrepreneurial Orientation and Innovation Strategy - Jefri Heridiansyah; Ariyani Indriastuti; Wahyudi; Catur Prabowo (Universitas Negeri Semarang, 2025)
This study explains innovation strategy's role in mediating entrepreneurial orientation's effect on MSME business performance. This research was conducted in MSME in Central Java, Indonesia. This analytical study explores empirical relationships using a descriptive observational, cross-sectional, deductive, and quantitative approach, statistical software Smart PLS, and a sample of 260 respondents. The analysis results show that entrepreneurial orientation also has a significant positive effect on innovation strategy, which in turn has a significant positive effect on MSME business performance. Entrepreneurial orientation has a significant positive effect on the performance of MSMEs. Innovation strategy has a mediating factor between entrepreneurial orientation and MSME business performance.